Degradation strategy of cyclin D1 in cancer cells and the potential clinical application - Chen, Shuyi; Li, Ling (Frontiers in Oncology, 2022)
Cyclin D1 has been reported to be upregulated in several solid and hematologic tumors, promoting cancer progression. Thus, decreasing cyclin D1 by degradation could be a promising target strategy for cancer therapy. This mini review summarizes the roles of cyclin D1 in tumorigenesis and progression and its degradation strategies. Besides, we proposed an exploration of the degradation of cyclin D1 by FBX4, an F box protein belonging to the E3 ligase SKP-CUL-F-box (SCF) complex, which mediates substrate ubiquitination, as well as a postulate about the concrete combination mode of FBX4 and cyclin D1. Furthermore, we proposed a possible photodynamic therapy strategythat is based on the above concrete combination mode for treating superficial cancer.